Study of Interaction of Glycerol Cryoprotectant and Its Derivatives with Dimethylacetamide in Aqueous Solution Using Fluorescent Probes - Dyubko, Tetiana; Pivovarenko, Vasyl; Chekanova, Valentina; Pakhomova, Yuliya; Hvozdiuk, Yana; Kompaniets, Antonina; Tatarets, Anatoliy (Problems of Cryobiology and Cryomedicine, 2021)
In this paper we have studied the interaction of the mixtures of glycerol (GL) and its oxyethylated derivatives (OEG) with polymerization degree n = 3, 25 and 30 with dimethylacetamide (DMAc) in aqueous solution using 3-hydroxy-4´-(N, N dimethylaminoflavone) fluorescent probe. The combination of GL and its oxyethylated derivatives with DMAc was found to reduce the membranotropy of certain cryoprotective agents, forming a mixture. The combination of both GL and its low molecular weight derivative (OEGn=3) with DMAc reduced the membranotropy of the latter. At the same time, combining GL derivatives of high molecular weight (OEGn=25 and OEGn=30) with DMAc diminished the membranotropy of OEG. The OEGn=30 at concentrations above 1 wt.% was shown to form the micellar-type structures or micellar associates in aqueous solution. This enabled suggesting the membranotropic ability of high molecular weight OEG associates to be stipulated by possible interaction of their nonpolar segments with nonpolar sites on biomembrane surface. Structural rearrangements of molecular associates in aqueous solutions of low and high molecular weight cryoprotectant mixtures were designated as the experimentally established mechanism of cytotoxicity reduction in combined cryoprotective media. Probl Cryobiol Cryomed 2021; 31(2): 139–150